The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1007/s00167-018-5237-3
|View full text |Cite
|
Sign up to set email alerts
|

Increased risk of ACL revision with non-surgical treatment of a concomitant medial collateral ligament injury: a study on 19,457 patients from the Swedish National Knee Ligament Registry

Abstract: Purpose To determine how concomitant medial collateral ligament (MCL) and lateral collateral ligament (LCL) injuries affect outcome after anterior cruciate ligament (ACL) reconstruction. Methods Patients aged > 15 years who were registered in the Swedish National Knee Ligament Registry for primary ACL reconstruction between 2005 and 2016 were eligible for inclusion. Patients with a concomitant MCL or LCL injury were stratified according to collateral ligament treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
126
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 117 publications
(129 citation statements)
references
References 44 publications
(58 reference statements)
2
126
0
1
Order By: Relevance
“…The football players in this cohort returned to play within a relatively short period, which suggests that the rehabilitation treatment was good and in line with what previous studies have reported after isolated MCL injuries [23, 27]. The MCL is an important stabiliser of the knee and, when injured in combination with the ACL, surgical treatment of the MCL may be necessary to restore knee joint stability [29], as a small increase in medial laxity may entail an increased risk of secondary consequences, such as the risk of ACL re-rupture and revision [30].…”
Section: Discussionsupporting
confidence: 82%
“…The football players in this cohort returned to play within a relatively short period, which suggests that the rehabilitation treatment was good and in line with what previous studies have reported after isolated MCL injuries [23, 27]. The MCL is an important stabiliser of the knee and, when injured in combination with the ACL, surgical treatment of the MCL may be necessary to restore knee joint stability [29], as a small increase in medial laxity may entail an increased risk of secondary consequences, such as the risk of ACL re-rupture and revision [30].…”
Section: Discussionsupporting
confidence: 82%
“…Perhaps, because of this, the present authors find the MCL the most difficult of the knee ligaments to reconstruct reliably. Registry data [ 31 ] have found that when an MCL injury in association with ACL rupture is treated conservatively, the likelihood of ACL graft failure is increased. These observations suggest the importance of improving the treatment of medial soft-tissue injuries.…”
Section: Introductionmentioning
confidence: 99%
“…A recent registry study reported that the non-surgical treatment of a concomitant MCL injury in the setting of an ACL reconstruction was associated with an increased risk of ACL revision; however, the impact of graft choice in this setting was not further investigated. 15 In addition, it is not known whether the preservation of the gracilis tendon may have a beneficial effect on the MCLdeficient knee, compared with harvesting both the ST and gracilis. The purpose of this study was therefore to compare the risk of ACL revision and the patientreported outcome after ACL reconstruction with a concomitant non-surgically treated MCL injury with regard to 3 ACL graft choices; the use of ST, the use of ST-G, and the use of patellar tendon (PT) autograft.…”
mentioning
confidence: 99%